Trademarks, brands, and competitiveness - Lopes, Teresa da Silva, 1968-; Duguid, Paul, 1954- (Routledge international studies in business history, 2010)
Examines trademarks and brands, and their historical role in national competitive and comparative advantage and in overall economic growth. This book provides an historical account of the contribution of brands in consumer goods to economic growth. It also examines the development of trademark law and its influence on brand strategy.